Spontaneous coronary artery dissection - Sharma, Ranjit; Rajbhandari, Rajeeb; Limbu, Yubraj; Singh, Satish; Bhatt, YKD; KC, Man Bahadur (Nepalese Heart Journal, 2013)
A 38 year old previously healthy woman was referred to ER for ongoing chest pain. She had sudden onset of central, crushing chest pain 3 h back and her ECG was found to have evidence of acute infero-lateral wall MI. There was no history of cardiovascular disease or identifiable CAD risk factors. She had a history of bone TB 10 y back. She was on oral contraceptive pills 5 y back. Her mother had hypertension and diabetes mellitus. Her father died at the age of 75 y due to unknown cause and had a history of hypertension. There is no history of hypertension, diabetes mellitus or CVD in her siblings. General Examination: O2 saturation-95%, Pulse-88bpm, Bp-110/90mmHg.Systemic Examination: no abnormality detected. Investigation: CBC, RFT, BSR, and Electrolytes were WNL. ECG: ST elevation in infero-lateral leads 3 h back but minimal ST elevation in lll and AVF in our ER. Cardiac Biomarkers: CPK-MB-50u/l and Trop + .Echo screening: hypokinetic apex, apical IVS and apical inferior LV wall. She was diagnosed as acute infero-lateral wall MI and was admitted in CCU was treated with Aspirin, Clopidogrel ,LMWH ,Atorvastatin ,IV GTN , Beta-Blocker, Anxiolytics ,PPI and Stool softener .She was well on first post MI day but suddenly developed chest pain on second post MI day and her ECG showed ST elevation in V3-V6. She was taken to Cath lab for rescue PCI. Her coronary angiography studies revealed a linear dissection involving the distal LAD with TIMI 3 distal flow (Fig1). She was conservatively management and was discharged on 7 post MI day. DOI: http://dx.doi.org/10.3126/njh.v9i1.8352 Nepalese Heart Journal Vol.9(1) 2012 pp.59-62